The connotations of the absence of feeling structures in the Koranic systems: Analytical rhetorical study - Al- Ghamdi, Sami Saleh (Journal of Humanities & Social Sciences, 2020)
This study focused on the conditions of absentees and cases of lack of feeling in each shrine, the importance of the study is to contribute to the management of the Koran and the development of the text and highlighting the text, by standing on the implications of structures; to enrich the aesthetics of this Koranic systems in the context of the palace, and then the implications of structures in the context of Igal, and then the implications Compositions in the context of the question, then the semantics of the compositions in the context of enabling the comma, and then the semantics of the compositions in the context of supplementation or precaution, and all this is done in an analytical inductive approach to the Quranic systems, with the use of vocabulary and structures and context, and the story of the Koran and its elements, verse and formulation, And the beginning of the verse and the middle and conclusion, then the researcher mentioned the results, such that the phrase (they do not feel) requires the current generally or common, has come to depict the attitudes of absentees live, Valmosofon not to feel infidels and polytheists and hypocrites only in two places, and other private and public results, then the researcher has developed two recommendations and an index of sources and references.